Germination and infection of Phakopsora pachyrhizi under simulated environment of the central area of Santa Fe, Argentina - Maumary, Roxana Lorena; Pioli, Rossana N.; Amsler, Alicia; Ivancovich, Antonio Juan (2017)
Soybean asian rust (SAR) caused by the fungus Phakopsora pachyrhizi was confirmed in Argentina for the first time during the 2002-2003 growing season. Then, the disease spread to the Northern and Eastern provinces, reaching the central area of Santa Fe, which is one of the main agricultural areas of the country. However, the disease has been usually detected at the end of the growing season (late March to early April), causing little or no impact on grain and seeds production. The objectives of this study were: i) characterize, molecularly and morphologically, the isolates of P. pachyrhizi from this area; ii) evaluate the effect of two environmental combinations (a typical for the region and other optimal as a control) on the germination of urediniospores in laboratory conditions; and iii) assess the infecting capacity of the inoculum obtained and the disease progress promoted under greenhouse conditions. Morphologic, molecular and pathometric characteristics of uredinia and urediniospores allowed verifying P. pachyrhizi identity. Uredospores exposed to daily temperatures ranging from 35 to 25°C, combined with a photoperiod and humidity conditions similar to those typical of the central area of Santa Fe during the crop cycle, decreased germination and appressoria formation and, consequently, SAR symptoms and uredinia production. These biological and epidemiological features would explain the erratic occurrence of SAR in the central producing area of Santa Fe, Argentina. Therefore, these could be used as references to design crop management strategies aimed at decreasing disease impact in other production areas